The elections and political realignments in Afghanistan - Ghulam Sakhi (Danish Institute for International Studies (DIIS), 2014)
[Introduction ...] This paper looks briefly at the status of the wider political alignments before nomination for the 5 April presidential election, assesses how and why all these alignments changed overnight by transforming into electoral tickets and what implications these realignments have for the future government and Afghan mainstream politics. In the run up to candidate nomination, the status of the opposition and political actors was as follows.
Keywords: 300